Tantangan dan Solusi Generasi Sandwich: Mengelola Tekanan Finansial dan Emosional - Daton Ardiyanto; Masduki Asbari; Margha Rizky Ristanto (Motivaksi: Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
The sandwich generation, namely individuals caught between the obligations of caring for their parents and their children, faces complex challenges, both financially and emotionally. In a TEDx presentation by Della Fadillah, this generation is described with a sandwich metaphor that describes the double burden they bear. This research uses descriptive qualitative methods with note-taking techniques to analyze the experiences of Fadillah, who from a young age had to support his family financially, overcome emotional difficulties, and prepare for the future with financial literacy. This article discusses how financial education and investment can be a way for the sandwich generation to achieve financial independence. The research results show that although this generation is faced with great challenges, hope and careful planning can help them break the cycle of dependency. Suggestions are given to strengthen financial literacy as a long-term solution.